Inventor Diasporas and the Internationalization of Technology - Miguelez Ernest (European Regional Science Association (ERSA), 2014)
This paper documents the influence of diaspora networks of high-skilled individuals ? i.e., inventors ? on international technological collaborations. By means of gravity models, it studies the determinants of the internationalization of inventive activity between a group of industrialized countries and a sample of developing and emerging economies. The paper examines in detail the influence exerted by skilled diasporas in fostering cross-country co-inventorship as well as R&D offshoring. The study finds a strong and robust relationship between inventor diaspora and different forms of international co-patenting. However, the effect is decreasing with the level of formality of the interactions. Interestingly, some of the most successful diasporas lately documented ? namely, Chinese and Indian ones ? do not govern the results. Migrant networks may smooth the obstacles to the internationalization of inventive activity. They create trust across national boundaries, provide information on market opportunities and, in general, reduce transaction costs of economic interactions between countries. Diaspora networks have been studied in the context of trade (Gould, 1994), FDI (Javorcik et al., 2011; Kugler and Rapoport, 2007), and international diffusion of ideas (Agrawal et al., 2011; Kerr, 2008). In parallel, numerous papers have investigated the internationalization of R&D activities (Guellec and van Pottelsberghe de la Potterie, 2001; Patel and Vega, 1999; Picci, 2010). To the best of my knowledge, however, no study has looked at the role of high-skilled diasporas in fostering international technological collaborations. To anticipate the results to come, I find a robust and sizeable effect of high-skilled diasporas on the internationalization of inventive activity between developed, receiving countries and developing, sending economies. The effect is statistically and economically significant: a 10-percent increase in the inventor diaspora abroad is associated with a 1.5 to 2.2 percent increase in international patent collaborations. The evidence found survives the inclusion of a large number of controls, fixed-effects (FE), robustness checks, and identification issues. Moreover, the effect is stronger for inventor-to-inventor collaborations ? co-inventorship ? than for applicant-to-inventor co-patents ? R&D offshoring, suggesting that diaspora effects mediate particularly interpersonal relations between co-workers.
Keywords: C8; J61; O31; O33; R0; 330